Determinants of Technological Quality in Online Commercial Services - Monika SZYDA (Communications of International Proceedings, 2021)
In article it is presented the essence of online commercial service, defined its quality and there are discussed quality attributes. Based on the studies of the literature, it has been proved that there is a gap in the research on the quality of online commercial services, especially in the technological dimension. Contribution of the paper is catalogue and characteristic of proposed determinants of online commercial services technological quality,  which may enrich the current methods of measuring quality. The conclusions were also confirmed by own research on the technological quality of websites of internet retailers and service providers, where the quality of online commercial services is often questionable. Paying more attention to the technological aspects of online store websites helps to improve the quality of online commercial services, providing better usability, functionality, efficiency and security, bringing benefits not only to consumers but also to owners of sales websites.
Keywords: Technological Quality; E-Commerce; Commercial Online Service; E-Service Quality Assessment; Customer Satisfaction